but the answer has to be x=1 or 3 or -1 or-2
13x-3=4x-4 Original problem
13x-4x= −4+3 Put same variable in same side
9x=-1 Simplify
9x/9=-1/9 Eliminate numbers at variables
x=-1/9
but the answer has to be x=1 or 3 or -1 or-2
13x-3=4x-4 Original problem
13x-4x= −4+3 Put same variable in same side
9x=-1 Simplify
9x/9=-1/9 Eliminate numbers at variables
x=-1/9
There's really only one way to solve this:
13x - 3 = 4x - 4
13x - 4x - 3 = 4x - 4x -4 (subtract 4x from both sides to get all x's on the same side)
9x -3 = -4
9x -3 +3 = -4 +3 (add 3 to both sides, to get x's alone)
9x = -1
9x/9 = -1/9 (divide both sides by 9, to get x alone)
x = -1/9 (minus one ninth)
Let's prove it, by making x in the original equation = -1/9:
(13)(-1//9) -3 = (4)(-1/9) - 4
-13/9 - 3 = -4/9 - 4
-13/9 + 4/9 = -4 + 3
-9/9 -1; -1 = -1 (proven - it works!)
If we try x=1, or x=3, or x=-1, or x=-2, it won't work (both sides of the equation will not be equal)
Let's try one of them, x=1, then you can try the other 3:
(13)(1) - 3 = (4)(1) - 4
13-3 = 4-4; or 10 = 0 (NOT! won't work; 10 does not equal zero)
13x - 3 = 4x - 4 Given
13x - 3 + 3 = 4x - 4 + 3 Add 3 to each side
13x + 0 = 4x - 4 + 3 Inverse property of addition
13x = 4x - 4 + 3 Identity property of addition
13x = 4x - 1 Simplify (-4 + 3 = -1)
13x - 4x = 4x - 4x - 1 Subtract 4 from each side
13x - 4x = 0 - 1 Inverse property of addition
13x - 4x = -1 Identity property of addition
9x = -1 Simplify (13x - 4x = 9x)
9x/9 = -1/9 Divide each side by 9
x = -1/9 Inverse property of multiplication
The answer cannot be any of the 4 that you have given.